Clinic-pathogenetic aspects of gingivitis in patients with crhonic infectious diseases (Эндодонтия Today, 2020)
With the purpose to study the mechanisms of formation and peculiarities of chronic gingivitis course in patients with chronic infectious diseases, the examination has been carried out of 45 patients with gingivitis on the background of HIV-infection, hepatitis C, chronic brucellosis; 15 patients with gingivitis without infectious diseases and 45 patients with infectious diseases without gingivitis. It was determined that in the patients with gingivitis and chronic infectious diseases the development of local inflammatory reaction is characterized by increased frequency of recurrence of gingivitis with its prolongation. The endogenous intoxication which is caused primarily by the chronic infectious diseases, play the main role in the forming of clinical specificity of gingivitis in patients with co-morbidities.